Penerapan Teknik-Teknik Komunikasi Persuasif Debt Collector dalam Penagihan Pembayaran Kredit Bermasalah di PT. Woori Finance Infonesia Cabang Kota Palu - Ramadani, Ria (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to determine the application of persuasive communication techniques used by debt collectors in collecting collections from problematic customers at PT. Woori Finance Indonesia Palu City Branch uses this qualitative descriptive method based on case study research using data collection and observation techniques, documentation and in- depth interviews with five informants selected using purposive sampling. Data analysis uses Interactive model analysis techniques (Miles and Hubernam). The results of this research show that there are 5 uses of effective persuasion communication techniques in persuading problem customers, 1.) Motivational appeal, 2.) Humorous appeal, 3.) Reward appeal, 4.) Emotional appeal, and 5.) fear appeal conveys.